Evaluación de protocolos de seguridad de las App de redes sociales en dispositivos móviles Android - García Molina, Teresa Maribel (2016)
The authors of the research consider the advances in technology and frequency of risks to which is exposed daily, conducting a study focused on security protocols mobile applications Android, proceeding to evaluate their respective metrics through analysis and / or monitoring of data packets sent and received from a mobile device to another and involvement. For this, it was necessary to use tools like Wireshark and Cain & Abel, the same that allowed the flow of information programs and obtain results for the corresponding protocols violated analysis, displayed and each encryptions time real. the research method-experimental method of measurement and methodology phased GQM (Goal Question Metric) which identified the most common vulnerabilities and metrics in the use of security protocols of the Apps when shipping was used or receipt of the information and gave scientific support in the period of display data on the parameters of tests performed respectively protocols, verifying that applications on Android are not completely vulnerable. Also one of the results shows that the safest in terms of data encryption protocol is HTTPS in mobile App that handle high data transfer and annexes reflected by photos the respective evaluation to achieve this result.